Ethical Consumption vs. Reducing Consumption: To what extent does Fair Trade merely act to deflect the attention away from the real problem of overconsumption? - Ulinski, Susanna (Momentum Quarterly, 2013)
This essay explores the alleged trade-off between reducing overconsumption and promoting ethical consumption, especially in the form of Fair Trade. While Fair Trade is primarily concerned with promoting greater equity in international trade, it does not address problems of ecological exhaustion through overconsumption. Furthermore, Fair Trade could promote increased consumption by inducing false consciousness among consumers. In this context, I propose an integrative approach of trying to address these two problems simultaneously by changing the social patterns of consumption, instead of interpreting them as diametrically opposed. Awareness is the first step in inducing a behavioural change. On an individual level, Fair Trade is fairly successful at creating sensational feedback processes, which increase the awareness for the social and environmental implications of individual consumer behaviour. Moreover, on an aggregate level, Fair Trade changes social patterns of consumption to promote ethical consideration in the context of consumer decision-making. Although Fair Trade is not primarily concerned with the level of consumption, it can help bring forth a change in consumption patterns in order to reduce overconsumption.
Keywords: overconsumption; ethical consumption; Fair Trade; consumer behaviour